Anterior Paraventricular Thalamus to Nucleus Accumbens Projection Is Involved in Feeding Behavior in a Novel Environment - Cheng, Jingjing; Wang, Jincheng; Ma, Xiaolin; Ullah, Rahim; Shen, Yi; Zhou, Yu-Dong (Frontiers in Molecular Neuroscience, 2018)
Foraging food in a novel environment is essential for survival. Animals coordinate the complex motivated states and decide whether to initiate feeding or escape from unfamiliar scenes. Neurons in the paraventricular thalamic nucleus (PVT) receive multiple inputs from the hypothalamus, forebrain, and caudal brainstem that are known to regulate feeding behavior. The PVT neurons also project to the forebrain regions that are involved in reward and motivation. Notably, the PVT neurons projecting to the nucleus accumbens (NAc) are activated when an incentive stimulus is presented. Optogenetic activation of the PVT-NAc path has been shown to increase the motivation for sucrose-seeking in instrumental tasks. However, how the PVT circuitry regulates the feeding behavior in a novel environment remains largely obscure. In the present study, we found that the activity of glutamatergic neurons in the anterior PVT (aPVT) projecting to the NAc dictates the novelty-suppressed feeding behavior in mice. Optogenetic activation of the aPVT-NAc projection increased the feeding time and food consumption in mice under a moderate food restriction in a novel open field where the food was placed in the central area. The exploratory and anxiety-like behaviors, however, were not altered by the aPVT-NAc activation. Our work reveals that activation of the aPVT-NAc pathway in mice generates a motivation to consume food in a novel environment.